Signal Alteration in the Optic Nerve Head on 3D T2-weighted MRI: a Potential Neuroimaging Sign of Glaucomatous Optic Neuropathy. (4th March 2018) - Lee, Jong Yeon; Kwon, Hyo Jeong; Park, Su Jin; Yoo, Chungkwon; Kim, Yong Yeon; Kim, Eung Yeop
ABSTRACT: Purpose : To investigate whether a signal alteration (SA) in the optic nerve head (ONH) on 3D T2-weighted magnetic resonance imaging (MRI) is associated with glaucomatous optic neuropathy Materials and Methods : A total of 35 patients with bilateral open-angle glaucoma and 31 age-matched controls underwent 3D high-resolution (0.98 × 0.98 × 1 mm 3 ) T2-weighted MRI and detailed ophthalmologic examinations including spectral-domain optical coherence tomography (OCT). Two independent reviewers blinded to subject data determined mild or prominent SA on 3D T2-weighted MRI for the incomplete or complete loss of ocular hypointense continuity in the ONH, respectively. The prevalence of SAs was compared between the two groups with the chi-square test. The OCT measurements were compared among the eyes with a mild or prominent SA and those without an SA using the Kruskal–Wallis test. Results : Of the 35 eyes with glaucoma, 26 eyes (74.3%) exhibited an SA in the ONH, whereas it was observed in 5 (16.1%) of the 31 controls ( P  < 0.001). The eyes with a prominent SA had a significantly different average retinal nerve fiber layer thickness ( P  = 0.002) and the ONH parameters except for the disk area (all P  < 0.001) than those without an SA. The eyes with a mild SA had a significantly narrower neural rim area, larger cup volume, and larger average and vertical cup-to-disk ratios compared with those without an SA ( P  = 0.011, 0.003, 0.004, and 0.004, respectively) Conclusions : The SA in the ONH on 3D T2-weighted MRI was significantly more frequent in eyes with open-angle glaucoma than in the controls.